Unraveling of Potential Targets for Andrographolide, Neoandrographolide and 5-hydroxy, 7-methoxy Flavone in the Treatment of Rheumatoid Arthritis using Network Pharmacology and Molecular Docking - Rana, Neha; Grover, Parul; Singh, Hridayanand; Rastogi, Sameer; Chawla, Pooja A. (Current Organic Chemistry, 2024)
Joint degeneration is a possible outcome of rheumatoid arthritis, an inflammatory disorder that is chronic, systemic, and progressive. Andrographis paniculata is known to contain many phytoconstituents that have demonstrated therapeutic effects in terms of inflammation. However, the therapeutic actions of Andrographis paniculata are still not fully understood. The present study aims to better understand rheumatoid arthritis and its possible treatments through the identification of relevant targets and mechanisms. A total of 47 common targets were identified for andrographolide, while 38 common targets were found for neoandrographolide. Additionally, 53 common targets were discovered for 5-hydroxy-7-methoxy flavone. Furthermore, a screening process was carried out to identify 9 primary hubb targets for andrographolide, neoandrographolide, and 5-hydroxy-7-methoxy flavone. Twenty useful gene ontology (GO) terms and twenty important Kyoto Encyclopaedia of Genes and Genomes (KEGG) pathways were found through the study of gene ontology and pathways. Molecular-docking analysis revealed that andrographolide had the highest binding efficacy (-7.8) towards the Serine/threonine-protein kinase 2 (PIM2) target. On the other hand, neoandrographolide displayed the highest binding efficacy towards mitogen-activated protein kinase (MAPK1) and Interlukine-6 (IL-6), with docking scores of (-9.0) and (-7.2), respectively. Furthermore, 5-hydroxy-7-methoxy flavone showed the highest docking score (-6.6) with Arachidonate 12-lipoxygenase (ALOX-12). The identification of numerous targets linked with various pathways in the treatment of Rheumatoid arthritis proves to be a helpful resource for future investigation into the mechanism and clinical applications of AP, NP, and 5H-flavone.
Keywords: Rheumatoid arthritis